The theology of ethnocultural empathic turn: getting to the core of sacralized crime - Sekulić, Branko (Lexington Books, Fortress Academic, 2024)
"The Theology of Ethnocultural Empathic Turn uncovers the roots of present-day ethnoreligious conflict, proposing an "ethnocultural empathy turn" inspired by ethnocultural empathy as a branch of social psychology and the example of Jesus' turn in Matthew 15:21-28, and advocating for liberation from the deadly deviation of Christianity's message"--